A comprehensive assessment of diversity loss in a well-documented tropical insect fauna: Almost half of Singapore's butterfly species extirpated in 160 years. (February 2020) - Theng, Meryl; Jusoh, Wan F.A.; Jain, Anuj; Huertas, Blanca; Tan, David J.X.; Tan, Hui Zhen; Kristensen, Nadiah P.; Meier, Rudolf; Chisholm, Ryan A.
Abstract: Insects as a group are suffering rapid declines in many parts of the world but are also poorly studied relative to vertebrate taxa. Comprehensive assessments of insect declines must account for both detected and undetected species. We studied extirpations among butterflies, a particularly well-known insect group, in the highly developed and biologically well-surveyed island city-state of Singapore. Building on existing butterfly species lists, we collated museum and naturalist records over the last two centuries and used statistical models to estimate the total extirpation rate since the first major collections in 1854. In addition, we compiled a set of traits for each butterfly species and explored how they relate to species discovery and extirpation. With a database of 413 native species, 132 (32%) of which are recorded as extirpated in Singapore, we used a statistical model to infer that, in addition, 104 unknown species (95% CI 60–162) were likely extirpated before they were ever discovered, suggesting a total extirpation rate of 46% (41–51%). In the trait analyses, we found that butterfly species that were discovered later were weakly associated with rarer larval host plants and smaller wingspans, while species that persisted for longer were weakly associated with higher larval host plant abundance and lower forest-dependence. This exercise is one of the first to offer a holistic estimate of extirpations for a group of insects by accounting for undetected extirpations. It suggests that extirpations among insects, specifically in the tropics, may be higher than naïve estimates based only on known records.